Reproducibility of the maximum accumulated oxygen deficit and run time to exhaustion during short-distance running - Doherty, M.; Smith, P. M.; Schroder, K. (Journal of Sports Sciences, 2000)
The aim of this study was to determine the reproducibility of the maximal accumulated oxygen deficit and the associated exercise time to exhaustion during short-distance running. Fifteen well-trained males (mean ± s: VO2max = 58.0 ± 4.6 ml.kg-1.min-1) performed the maximum accumulated oxygen deficit test at an exercise intensity equivalent to 125% VO2max. The test was repeated at the same time of day on three occasions within 3 weeks. There was no significant systematic bias between trials for either maximum accumulated oxygen deficit (mean ± s: trial 1 = 69.0 ± 13.1; trial 2 = 71.4 ± 12.5; trial 3 = 70.4 ± 15.0 ml O2 Eq.kg-1; ANOVA, F = 0.70, P = 0.51) or exercise time to exhaustion (trial 1 = 194 ± 31.1; trial 2 = 198 ± 33.2; trial 3 = 201 ± 36.8 s; F = 1.49, P = 0.24). In addition, other traditional measures of reliability were also favourable. These included intraclass correlation coefficients of 0.91 and 0.87, and sample coefficients of variation of 6.8% and 5.0%, for maximum accumulated oxygen deficit and exercise time to exhaustion respectively. However, the '95% limits of agreement' were 0 ± 15.1 ml O2 Eq (1.01 × / ÷ 1.26 as a ratio) and 0 ± 33.5 s (1.0 × / ÷ 1.18 as a ratio) for maximum accumulated oxygen deficit and exercise time to exhaustion respectively. We estimate that the sample sizes required to detect a 10% change in exercise time to exhaustion and maximum accumulated oxygen deficit after a repeated measures experiment are 10 and 20 respectively. Unlike the results of previous maximum accumulated oxygen deficit studies, we conclude that it is not a reliable measure.